2017
DOI: 10.1038/srep40619
|View full text |Cite
|
Sign up to set email alerts
|

Californium-252 neutron intracavity brachytherapy alone for T1N0 low-lying rectal adenocarcinoma: A definitive anal sphincter-preserving radiotherapy

Abstract: This study evaluated the 4-year results of 32 patients with T1N0 low-lying rectal adenocarcinoma treated solely with californium-252 (Cf-252) neutron intracavity brachytherapy (ICBT). Patients were solicited into the study from January 2008 to June 2011. All the patients had refused surgery or surgery was contraindicated. The patients were treated with Cf-252 neutron ICBT using a novel 3.5-cm diameter off-axis 4-channel intrarectal applicator designed by the authors. The dose reference point was defined on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Nowadays, 252 Cf has been used as a source of brachytherapy in treating patients with cervical, esophageal, and some other types of cancer. Our previous study also suggested a promising result of 252 Cf neutron ICBT alone in rectal cancer patients with T1N0 rectal cancer (9). To our knowledge, the efficacy and safety profile of 252 Cf neutron ICBT in treating T2N0-1 or T3N0-1 rectal cancer patients have not been documented.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Nowadays, 252 Cf has been used as a source of brachytherapy in treating patients with cervical, esophageal, and some other types of cancer. Our previous study also suggested a promising result of 252 Cf neutron ICBT alone in rectal cancer patients with T1N0 rectal cancer (9). To our knowledge, the efficacy and safety profile of 252 Cf neutron ICBT in treating T2N0-1 or T3N0-1 rectal cancer patients have not been documented.…”
Section: Introductionmentioning
confidence: 89%
“…The fixed four fractions were implemented with a total neutron brachytherapy dose of 40–45 Gy (11–14 Gy/f/w) at the dose reference point defined on the anal canal mucosal surface during the EBRT. The dose calculation method and detailed operation procedures of 252 Cf neutron ICBT were described in our previous study ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…252 Cf is a suitable neutron brachytherapy source because of its long half-life (2.6 years) and relatively high neutron yield (Wierzbicki et al 1997). The advantages and limitations of using 252 Cf source for various brachytherapy applications were reported elsewhere (Maruyama and Beach 1986, Maruyama et al 1991, Wierzbicki et al 1994, Abd El-Hafez et al 1997, Rivard 2000, Ghassoun et al 2010, Lei et al 2011, Ghassoun 2013, Yadollahpour et al 2015, Zhou et al 2016, Qian et al 2017, Xiong et al 2017, Rasouli et al 2020, Karimi-Shahri et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Radionuclides with high heat generation ( 238 Pu and 244 Cm) are used in radioisotope thermoelectric generators, allowing one to produce electricity even outside the Solar System . Another area of interest in actinides is nuclear medicine, where the α-emitter 225 Ac , is considered to be a perspective for cancer treatment and 252 Cf is already used as the basis of neutron sources. It is important that manmade actinides have been released into the environment because of their use in nuclear detonations and several accidents at the nuclear power plants, reprocessing facilities, satellites, etc.…”
Section: Introductionmentioning
confidence: 99%